Regulatory bottlenecks, transaction costs and corruption: a cross-country investigation - Rajeev K. Goel (Bank of Finland, Institute for Economies in Transition (BOFIT), 2008)
This paper uses recent data on a large cross-section of countries to study the determinants of corrupt activity. The main contribution is to examine the effects of different types and severities of government regulations on corrupt activities. The results show that greater prosperity and democracy lead to less corrupt activity. Variables representing the degree of fractionalization across three dimensions and least developed nations are statistically insignificant. Having more regulation, including number of procedures and time involved across four categories (business startup, licensing, property registration, and taxation), leads to greater corruption. More regulatory procedures, especially for business startups and property registrations, have the most corruption-enhancing effect. Whereas lengthier procedures also generally spur corruption, there are important differences. Finally, higher regulatory transactions costs do not seem to significantly impact corruption. Policy implications are discussed.
URN:NBN:fi:bof-201408072167
Keywords: H26; H87; K42; 330; Corruption; Business startup; Licenses; Property; Taxes; Fractionalization; De-mocracy; Prosperity